Port of Spain (Trinidad) - Palm Tree (Six sisters) - (:unkn) unknown (My University, 2010)
The postcard shows cows eating grass near palms trees in the Queen's Park Savannah in Port of Spain, Trinidad. Postcard number 9.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Mountains--Trinidad and Tobago; Savannas--Trinidad and Tobago; Palms--Trinidad and Tobago; Cattle--Trinidad and Tobago; [1911]; Trees--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Grazing--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)